Jewish Warsaw - Jewish Berlin : Literary Portrayal of the City in the First Half of the 20th Century. - Brzostowska, Anna.; Giebułtowski, Jerzy; Molisak, Alina (Frankfurt a.M. : Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2021)
The book deals with the Jewish presence in the first half of the 20th century in two cities - Warsaw and Berlin. The analyzed and described material consists of literary works of selected authors. Particular attention was paid to the formation of modern Jewish identities in both capitals.
Cover -- Series Information -- Copyright Information -- Dedication -- Table of Contents -- Foreword -- Two Cities - Two Quarters -- City and Politics -- Supplement: City and Politics, That Is, Literary Political Fiction191 -- City and Religion -- City and Vice -- City Divided and Contact Zones -- City and Emigration -- Concluding Remarks: City and Variants of Identity -- Bibliography -- Internet Sources -- Index of People -- Series Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books